2018
DOI: 10.1177/1940082918756816
|View full text |Cite
|
Sign up to set email alerts
|

Rheophytes of the Samaná Norte River, Colombia: A Hydroelectric Project Threatens an Endemic Flora

Abstract: We studied the rheophytic vascular flora of the Samaná Norte River basin in Antioquia, Colombia, by rafting along a 61.4-km stretch of the river and establishing 10 plots on its banks. We found 58 species of rheophytes, including morphospecies, belonging to 29 families, mostly herbs and subshrubs. At least nine of the species are known only from this river basin and seven of them were discovered as new to science during this study. The nine species endemic to this river basin have estimated area of occupancy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…Rheophytic woody plants (e.g., Coffeacongensis Froehn and Breonadiasalicina (Vahl) Hepper & Wood in the Rubiaceae) are known to occur outside the study area in Africa. Rheophyte diversity, according to some authors e.g., van Steenis (1981) and Hoyos-Gomez and Bernal (2018), is high in South East Asia and South America compared with tropical Africa. A survey of rheophytes of Africa by Ameka et al (2002) found 53 rheophytes including 33 Podostemaceae species in Cameroon.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Rheophytic woody plants (e.g., Coffeacongensis Froehn and Breonadiasalicina (Vahl) Hepper & Wood in the Rubiaceae) are known to occur outside the study area in Africa. Rheophyte diversity, according to some authors e.g., van Steenis (1981) and Hoyos-Gomez and Bernal (2018), is high in South East Asia and South America compared with tropical Africa. A survey of rheophytes of Africa by Ameka et al (2002) found 53 rheophytes including 33 Podostemaceae species in Cameroon.…”
Section: Discussionmentioning
confidence: 96%
“…Rheophyte, a term coined by van Steenis in 1932 (van Steenis 1978), is used to describe an aquatic plant which is in nature restricted to swift-running rivers and streams and grows up to flood level, but not beyond the reach of regularly occurring flash floods (van Steenis 1978, 1981). Rheophytes occur worldwide but are found particularly in evergreen rain forests, where they are the dominant aquatic macrophytes in tropical river systems (van Steenis 1978, Quiroz et al 1997, Ameka 2000, Hoyos-Gomez and Bernal 2018). Members of this biological group of plants are not necessarily taxonomically related, but they show a common adaptation to a restricted ecological habitat or environmental factors (van Steenis 1981, Ameka 2000, Ameka et al 2002, Hoyos-Gomez and Bernal 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…En Colombia, por ejemplo, se suman estudios de proyectos hidroeléctricos sobre la Hidroeléctrica el Quimbo [15] e Hidrosogamoso [16]: estos casos confirman, al igual que Hidroituango, el declive del territorio y la incertidumbre que generan entre las comunidades y hacia el ecosistema. A su turno, y en relación con el caso del proyecto hidroeléctrico previsto sobre el Río Samaná Norte, Hoyos y Rodríguez muestran la posible pérdida de especies endémicas y desconocidas, inclusive por los estudios hasta ahora recibidos por la Autoridad Nacional de Licencias Ambientales [17].…”
Section: Los Proyectos De Desarrollo Hidroeléctricounclassified